The Prospects for Processing Reservoir Oil Sludge into Hydrocarbons by Low-Temperature Hydrogenation in Sorbing Electrochemical Matrices in Comparison with Conventional High-Temperature Hydrocracking - Anton Maximov; Aslan Tsivadze; Alexander Fridman; Tatyana Kuchinskaya; Alexander Novikov; Maxim Shabanov; Evgeny Naranov (Energies, 2020)
In this paper, we developed an effective method for purifying oil sludge using a sorbing electrochemical matrix and assessed the prospects of this method in comparison with conventional hydrocracking. We synthesized Ni-W supported hydrocracking catalysts with different morphology and studied their activity under various conditions, we compared the obtained catalysts with commercial catalyst SGK-5. We demonstrated that the introduction of a secondary mesoporous structure in the catalyst leads to an increase in the yield of light fractions to 52 wt.%. The possibility is demonstrated to obtain hydrocarbons from reservoir oil sludge, dispersed into an aqueous solution of detergent, by the method of low-temperature hydrogenation in sorbing electrochemical matrices. The obtained product was characterized by low viscosity, low content of transition metals (<320 ppm), and sulphur (<260 ppm).